500-A LaB6 Hollow cathode for high power electric thrusters. (April 2022) - Becatti, Giulia; Goebel, Dan M.
Abstract: NASA continues to develop higher power ion and Hall thrusters for deep space human and robotic missions that require higher thrust and specific impulse than available in current thrusters. The NASA XR-100 nested Hall thruster successfully operated at 100 kW of power; driven by a JPL LaB6 hollow cathode that produced up to 250 A of discharge current in the thruster and 25–350A in the cathode test facility. The next generation of this LaB6 hollow cathode has been designed and built at JPL and tested at up to 500 A of discharge current. Extending the current to this high level was challenging, with iterations in the design necessary to provide adequate thermal isolation of the insert to lower the heater power required to ignite, to achieve sufficient keeper discharge current to aid in the startup, and to maintain the cathode orifice plate at acceptable temperatures during very high current operation. The 2nd generation version of the cathode successfully achieved 500 A of discharge current operation with low high-energy ion content. Discussions of the plasma instabilities observed in the plume, the plasma penetration into the insert region, and cathode life are provided. Highlights: Lanthanum hexaboride hollow cathode capable of 500 A discharge currents developed. Optimizations aimed at reducing the heater power and enabling ignition and large discharge current range operation discussed. Techniques shown to produce low energetic ion production at high discharge currents. Instabilities in the cathode plume at high currents disclosed and discussed.